Membangun Kesadaran Ekologis Warga Sekolah Melalui IHT Tatanen di Bale Atikan di SDN 3 Nangewer Kecamatan Darangdan Kabupaten Purwakarta - Wulandari, Dyah; Narkum, Narkum; Supendi, Dede; Mukti, Saepul; Setiawan, Usep (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This community service aims to increase ecological understanding and awareness at SDN 3 Nangewer which is carried out by holding IHT Tatanan activities in Bale Atikan. This is based on the problem that it is still lowecological understanding and awarenessat SDN 3 Nangewer. This research was conducted using descriptive-quantitative research where the service method used a mix method approach with a Participatory Action Research (PAR) design. The first is to observe the problems that occur, the second is to analyze the problems that occurSDN 3 Nangewerand followed by the next step systematically by taking action in the form of preparing material for IHT Tatanen activities in Bale Atikan and then observing the increase in ecological understanding and awareness at SDN 3 Nangewer. With the IHT Tatanan activities in Bale Atikan carried out at SDN 3 Nangewer, the ecological understanding and awareness of IHT participants has increased.